Solvent Extraction Method for Separation and Determination of Zn (||) by Using of Imidazole Derivative - K. Jawad, Shawket; Sahib Mohummed Husien, Nemah (International Journal of Engineering and Technology, 2018)
Solvent extraction as sensitive and effective method for separation, pre concentration andÂ determination Zn+2 after converted the cation into ion pair complex by combination, coordinately with complexion agent 2-[(2-methylphenyl)azo]-4,5-diphenyl imidazol (MPADPI). Spectrophotometric study shows wave length for maximum absorbance of complication reagent equal to Î»max= 405nm but maximum absorbance wave length for ion pair complex extracted of Zn+2 equal to Î»max=535nm. The experimental studies for pin point the optimum conditions of extraction shows pH=10 in presence 50Âµg Zn+2 in 5mL with shaking time equal 10 min., by using slope analysis method and mole ratio method demonstrated the structure of the ion pair association complex was[1:1]2+;2Cl-,[MPADPI-Zn]2+;2Cl-. The experimental study about organic solvent effect shows there was not any linear relation between dielectric constant of organic solvent and the values that means there was not any effect for polarity of organic solvent on extraction efficiency but there was un effect for organic solvent structure .Temperature effect study shows the extraction method was exothermic behavior withÂ thermodynamic factor equal toÂ Î”Hex=-0.0255kJmol-1, Î”Gex =-19.4005 kJmol-1,Î”Sex 69.78 J molK-1 and other studies involved synergism effect, methanol effect ,spectrophotometric determination of Zn+2 in different samples.Â